Bedaquiline reprograms central metabolism to reveal glycolytic vulnerability in Mycobacterium tuberculosis - Jared S. Mackenzie (Nature Portfolio, 2020)
Bedaquiline (BDQ) is a known tuberculosis treatment, but the precise mechanism of cell death is unclear. Here, the authors explore the metabolic profiles of M. tuberculosis upon BDQ treatment and find reliance on glycolysis and synergistic cell death when oxidative phosphorylation is also targeted.